Characteristic indicators of cardiorespiratory system of students engaged in kettlebell lifting - Magliovanyy A.V; Shymechko I.M; Boyarchuk A.M; Ivanochko O.Y (Kharkov National Pedagogical University, 2011)
The research of level of functional possibilities of students (17-22 years old, n=37), which got busy in the university section from weight sport, by the indexes of frequency of cardiac abbreviations, restoration processes, vital capacity, test Shtange, index Robinsona and level of physical capacity is considered in the article. The changes of the explored indexes of students with a different level of preparedness (different digits) are analyzed. It is definite, that in the process of employments by weights sport the improvement of functional possibilities takes place. Thus with the in-plant training there are more expressed positive changes of indexes of the basic systems of students organism.